Spillover from the haven: Cross-border externalities of patent box regimes within multinational firms - Thomas Schwab; Maximilian Todtenhaupt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
This paper analyzes externalities of patent box regimes in Europe. Tax reductions in foreign affiliates of a firm that also provide a profit shifting opportunity reduce the user cost of capital and thereby increase domestic investment. We test this mechanism for the case of research activity. By combining information on patents, firm ownership data and specific characteristics of patent box regimes, we show that patent box regimes without nexus requirements for tax-efficient reallocation of patent profits induce positive spillovers within multinational groups. The implementation of a patent box in a country one of the foreign affiliates of a firm resides, increases domestic research activity by about 74 percent or 2 percent per implied tax rate differential. Furthermore, our findings suggest that patent boxes generate negative spillovers on average patent quality. This has important implications for international tax policy and the evaluation of patent box regimes.
urn:nbn:de:bsz:180-madoc-415602
Keywords: F23; H25; O31; 330; patent box; spillover; corporate taxation; innovation